Protective effect of N-acetylcysteine on renal ischemia/reperfusion injury in the rat - (:unkn) unknown (SPRINGER HEIDELBERG, 2003)
Background: Oxygen free radicals are important components involved in the pathophysiological tissue alterations observed during ischemia/reperfusion (I/R). Methods: The protective effect of N-acetylcysteine (NAC) against the damage inflicted by reactive oxygen species during renal I/R. was investigated in Wistar Albino rats using biochemical parameters. Animals were unilaterally nephrectomized, and subjected to 45 min of renal pedicle occlusion followed by 1h of reperfusion. N-acetylcysteine (150 mg/kg, i.p.) or vehicle was administered twice, 15 min prior to ischemia and immediately before the reperfusion period. At the end of the reperfusion period, rats were killed by decapitation. For biochemical analysis, the lipid peroxidation product malondialdehyde (MDA) and glutathione (GSH) levels, myeloperoxidase (MPO) activity and protein oxidation (PO) were tested. Serum creatinine and BUN concentrations were measured for the evaluation of renal function. Results: I/R induced nephrotoxicity, as evidenced by increases in BUN and creatinine, was reversed by NAC. The decrease in GSH and increases in MDA, MPO and PO induced by I/R indicated that renal injury involves free radical formation. Conclusions: Since NAC reversed these oxidant responses, and protected rat renal proximal tubules from in vitro simulated reperfusion injury, it seems that NAC protects kidney tissue against oxidative damage.
Keywords: N-acetylcysteine; kidney; ischemia/reperfusion; lipid peroxidation; glutathione; myeloperoxidase; protein carbonylation; ISCHEMIA-REPERFUSION INJURY; LIPID-PEROXIDATION; TISSUE-INJURY; FREE-RADICALS; FAILURE; GLUTATHIONE; ANTIOXIDANT; MELATONIN; PREVENTION; KIDNEY